Influence of regional biomass burning on the highly elevated organic carbon concentrations observed at Gosan, South Korea during a strong Asian dust period - Duc Luong Nguyen; Kim, Jin Young; Ghim, Young Sung; Shim, Shang-Gyoo (SPRINGER HEIDELBERG, 2015)
PM2.5 carbonaceous particles were measured at Gosan, South Korea during 29 March-11 April 2002 which includes a pollution period (30 March-01 April) when the highest concentrations of major anthropogenic species (nss-SO4 (2-), NO3 (-), and NH4 (+)) were observed and a strong Asian dust (AD) period (08-10 April) when the highest concentrations of mainly dust-originated trace elements (Al, Ca, Mg, and Fe) were seen. The concentrations of elemental carbon (EC) measured in the pollution period were higher than those measured in the strong AD period, whereas an inverse variation in the concentrations of organic carbon (OC) was observed. Based on the OC/EC ratios, the possible source that mainly contributed to the highly elevated OC concentrations measured in the strong AD period was biomass burning. The influence of the long-range transport of smoke plumes emitted from regional biomass burning sources was evaluated by using MODIS (Moderate Resolution Imaging Spectroradiometer) satellite data for fire locations and the potential source contribution function analysis. The most potential source regions of biomass burning were the Primorsky and Amur regions in Far Eastern Russia and southeastern and southwestern Siberia, Russia. Further discussion on the source characteristics suggested that the high OC concentrations measured in the strong AD period were significantly affected by the smoldering phase of biomass burning. In addition to biomass burning, secondary OC (SOC) formed during atmospheric long-range transport should be also considered as an important source of OC concentration measured at Gosan. Although this study dealt with the episodic case of the concurrent increase of dust and biomass burning particles, understanding the characteristics of heterogeneous mixing aerosol is essential in assessing the radiative forcing of aerosol.
Keywords: SINGLE-PARTICLE CHARACTERIZATION; AIR-POLLUTION SOURCES; LONG-RANGE TRANSPORT; CHEMICAL-COMPOSITION; URBAN SITE; PHYSICAL-PROPERTIES; ELEMENTAL CARBON; FINE PARTICLES; BLACK CARBON; AEROSOL